2017
DOI: 10.1039/c7tb00766c
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Raman spectroscopy as an enabling tool for long-term intracellular studies of nanomaterials at nanomolar concentration levels

Abstract: Imaging of individual SWCNTs inside neural stem cells has been demonstrated using confocal scanning Raman microscopy. Hyperspectral Raman imaging allowed detection of nanomaterials applied to the cell in ultra-low doses in long-term studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 91 publications
0
12
0
Order By: Relevance
“…The average length of carbon nanotubes in our sample is 166 nm . We estimate that the average mass of a nanotube of this length (using the (6,5) species) is 3 × 10 –19 g, based on previous calculations . Thus, for one nanotube, we calculate that approximately 180 molecules of doxorubicin bound strongly.…”
Section: Results and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The average length of carbon nanotubes in our sample is 166 nm . We estimate that the average mass of a nanotube of this length (using the (6,5) species) is 3 × 10 –19 g, based on previous calculations . Thus, for one nanotube, we calculate that approximately 180 molecules of doxorubicin bound strongly.…”
Section: Results and Discussionmentioning
confidence: 90%
“…44 We estimate that the average mass of a nanotube of this length (using the (6,5) species) is 3 × 10 −19 g, based on previous calculations. 45 treatment with buffer, 500 μM Dox, or 500 μM doxorubicin followed by three washes, to assess the impact of washing on the nanotube optical response to doxorubicin (Figure S6c). We observed that the emission spectrum was largely unaltered by washing as compared to the sample containing 500 μM doxorubicin without pelleting and washing (Figure S6d).…”
Section: Nano Lettersmentioning
confidence: 99%
“…In addition, the Raman spectrum was collected using confocal micro-Raman spectroscopy (WITec Control FIVE software). [86] The single-point spectrum was collected with an integration time of 0.1 s.…”
Section: Methodsmentioning
confidence: 99%
“…AFM was performed in tapping mode on dry samples with an AFM tip from Nanoworld: NCST, silicon, f o = 160 kHz, C = 7.4 N m −1 ). In addition, the Raman spectrum was collected using confocal micro‐Raman spectroscopy (WITec Control FIVE software) . The single‐point spectrum was collected with an integration time of 0.1 s.…”
Section: Methodsmentioning
confidence: 99%
“…Such a functionalization facilitates NT entry via endocytosis upon introduction in vitro ( 10 , 12 ) and preserves NT material dispersal in the form of individual tubes, as opposed to some earlier works ( 9 , 13 , 14 , 15 , 16 ). Biophysical characterization of the SWCNTs used can be found in our previous publications ( 17 , 18 ). Our previous studies in C17.2 neural progenitor cells (NPCs) allowed us to define the acceptable range of DNA-SWCNT concentrations (10 pM or lower) to be used for biological applications.…”
Section: Introductionmentioning
confidence: 99%